Transpulmonary Pressure-Guided Lung-Protective Ventilation Improves Pulmonary Mechanics and Oxygenation Among Obese Subjects on Mechanical Ventilation. - Rowley, Daniel D.; Arrington, Susan R.; Enfield, Kyle B.; Lamb, Keith D.; Kadl, Alexandra; Davis, John P.; Theodore, Danny J. (Respiratory Care, 2021)
BACKGROUND: Transpulmonary pressure (PL) is used to assess pulmonary mechanics and guide lung-protective mechanical ventilation (LPV). PL is recommended to individualize LPV settings for patients with high pleural pressures and hypoxemia. We aimed to determine whether PL-guided LPV settings, pulmonary mechanics, and oxygenation improve and differ from non-PL-guided LPV among obese patients after 24 h on mechanical ventilation. Secondary outcomes included classification of hypoxemia severity, count of ventilator-free days, ICU length of stay, and overall ICU mortality. METHODS: This is a retrospective analysis of data. Ventilator settings, pulmonary mechanics, and oxygenation were recorded on the initial day of PL measurement and 24 h later. PL-guided LPV targeted inspiratory PL < 20 cm H2O and expiratory PL of 0--6 cm H2O. Comparisons were made to repeat measurements. RESULTS: Twenty subjects (13 male) with median age of 49 y, body mass index 47.5 kg/m², and SOFA score of 8 were included in our analysis. Fourteen subjects received care in a medical ICU. PL measurement occurred 16 h after initiating non-PL-guided LPV. PL-guided LPV resulted in higher median PEEP (14 vs 18 cm H2O, P = .009), expiratory PL (--3 vs 1 cm H2O, P = .02), respiratory system compliance (30.7 vs 44.6 mL/cm H2O, P = .001), and PaO2/FIO2 (156 vs 240 mm Hg, P = .002) at 24 h. PL-guided LPV resulted in lower FIO2 (0.53 vs 0.33, P < .001) and lower PL driving pressure (10 vs 6 cm H2O, P = .001). Tidal volume (420 vs 435 mL, P = .64) and inspiratory PL (7 vs 7 cm H2O, P = .90) were similar. Subjects had a median of 7 ventilator-free days, and median ICU length of stay was 14 d. Three of 20 subjects died within 28 d after ICU admission. CONCLUSIONS: PL-guided LPV resulted in higher PEEP, lower FIO2, improved pulmonary mechanics, and greater oxygenation when compared to non-PL-guided LPV settings in adult obese subjects. Key words: mechanical ventilation; obesity; respiratory mechanics; esophageal pressure;